1975
DOI: 10.1063/1.321312
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric properties of cuprous oxide

Abstract: The effects of transient and steady-state illumination on the electrical properties of single-crystal cuprous oxide have been investigated in the temperature range from 230 to -20°C. For samples equilibrated well within the region of Cu,O stability, conduction was governed by an acceptor level at 0.4 eV above the valence band as determined from the temperature dependence of the Hall effect. The presence of two minority carrier trapping levels was also established and trapping parameters were determined from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 12 publications
2
72
0
Order By: Relevance
“…One violet and two blue emission peaks around 421 nm ͑2.94 eV͒, 440 nm ͑2.81 eV͒, and 469 nm ͑2.64 eV͒ are found for the sample CP1 having crystallite diameter ϳ16 nm. These emissions are expected due to the excitonic transitions from the different sub levels of the CB to the Cu d-shells of the VBs, 8,34 which will be discussed later using schematic band diagram. All the peaks were blue shifted with decreasing the size of the nanoparticles, indicating the quantum confinement effect of the excitonic transition expected for Cu 2 O nanoparticles.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…One violet and two blue emission peaks around 421 nm ͑2.94 eV͒, 440 nm ͑2.81 eV͒, and 469 nm ͑2.64 eV͒ are found for the sample CP1 having crystallite diameter ϳ16 nm. These emissions are expected due to the excitonic transitions from the different sub levels of the CB to the Cu d-shells of the VBs, 8,34 which will be discussed later using schematic band diagram. All the peaks were blue shifted with decreasing the size of the nanoparticles, indicating the quantum confinement effect of the excitonic transition expected for Cu 2 O nanoparticles.…”
Section: -mentioning
confidence: 99%
“…Quantum confinement of electrons in the nanoparticles gives rise to the splitting of energy levels with respect to bulk. 8,46,47 Thus the relaxations of the electrons occur from the different subenergy levels of O 2p band to Cu 3d band, which give rise one violet and two blue emissions. ͑Fig.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Cu 2 O and CuO nanosystems have great potential for photo-activated hydrogen production, a key solution for the clean and recyclable H 2 energy. There are several reports on the growth, characterization and applications of copper 2 oxides, however, the electrical characteristics of the copper oxide films are strongly influenced by the preparation methods [3]. There are numerous reports on the exploitation of Cu 2 O as an active layer for solar cells [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the techniques produce p-type conducting thin films. Many theoretical and experimental studies (Guy, 1972;Pollack & Trivich, 1975;Kaufman & Hawkins, 1984;Harukawa et al, 2000;Wright & Nelson, 2002;Paul et al, 2006) have been revealed that the Cu vacancies originate the p-type conductivity. However, electrodeposition (Siripala & Jayakody, 1986, Siripala et al, 1996Wijesundera et al, 2000;Wijesundera et al, 2006) of Cu 2 O thin films in a slightly acidic aqueous baths produce n-type conductivity.…”
Section: Introductionmentioning
confidence: 99%